Paraneoplastic pyoderma gangrenosum in solid organ malignancy: a literature review. (12th September 2019) - Shah, Monica; Sachdeva, Muskaan; Gefri, Amnah; Jfri, Abdulhadi
Abstract: Pyoderma gangrenosum (PG) is a rare destructive, ulcerative, and inflammatory cutaneous disease. PG can be associated with inflammatory bowel disease (IBD), arthritis, autoinflammatory syndromes, and hematological malignancies. Multiple reports in the literature have found an association between PG and solid organ tumors. This article provides a summary and review of PG in patients with solid organ malignancies. We performed a PubMed search using the terms pyoderma gangrenosum, paraneoplastic pyoderma gangrenosum, cancer, malignancy, tumor, and solid organ malignancy. Out of 529 papers screened, 19 relevant cases were included that reported patients above the age of 12 years old with antecedent, coincident, or subsequent occurrence of PG in association with a solid organ malignancy. The most common malignancies associated with PG were found in the breast ( n  = 6, 31.6%). In a majority of the cases, the site of PG was found to be the lower extremities ( n  = 12, 63.2%). Almost all cases were presented with ulcerative PG subtype ( n  = 18, 94.7%). Moreover, 78.9% of cases ( n  = 15) were reported to have PG prior to tumor diagnosis. PG lesions resolved in 100% of patients after either tumor or PG‐specific treatment. We identified a strong temporal relationship between ulcerative PG and its associated solid organ malignancy. Other associations with breast cancer and lower extremity location exist but are not as strong.